Phytoplankton in the Anchialine Habitat of Red Shrimp (Parhippolyte uveae) at Mangrove Ecosystem Waters - Findra, Muhammad Nur; Rahman, Arif; Sara, La; Cahyani, Waode Sitti; Meilana, Lusita (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The anchialine habitat waters of this study is located at mangrove ecosystem around Koguna Beach area, Buton Island, Indonesia. It is a closed water, isolated from the sea, and inhabited by Parhippolyte uveae red shrimp. The existence of phytoplankton in this habitat can be used to determine the availability of natural food and the water quality of this shrimp’s habitat. This study was conducted to examine the presence of phytoplankton in the anchialine habitat of red shrimp. Phytoplankton samples were obtained by filtering water using Plankton Net. Meanwhile, several biological indexes such as the diversity index, evenness index, and dominance index were used to analyze the phytoplankton community. The result showed that this habitat was dominated by phytoplankton from the classes Bacillariophyceae, Florideophyceae, and Globothalamea with a total of 13 genera in September 2021 and Bacillariophyceae, Cyanophyceae, Dinophyceae, and Globothalamea with a total of 18 genera in December 2021. The most common type of phytoplankton found in the red shrimp habitat during the study was Navicula sp. with a ban of 1436 cells L-1 and 479 cells L-1 in September 2021 and December 2021, respectively. The diversity index of phytoplankton in this habitat was low, meanwhile, the index of evenness and dominance indicated that this habitat was of good quality (evenness index was high and dominance index was low). This study can be used as a basic information for further research on the management control for this species habitat.